2008
DOI: 10.4049/jimmunol.180.5.3103
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Renal Allograft Acceptance Associated with “Regulatory” Dendritic Cells and IDO

Abstract: MHC-mismatched DBA/2 renal allografts are spontaneously accepted by C57BL/6 mice by poorly understood mechanisms, but both immune regulation and graft acceptance develop without exogenous immune modulation. Previous studies have shown that this model of spontaneous renal allograft acceptance is associated with TGF-β-dependent immune regulation, suggesting a role for T regulatory cells. The current study shows that TGF-β immune regulation develops 30 days posttransplant, but is lost by 150 days posttransplant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 57 publications
9
61
0
Order By: Relevance
“…5C). Therefore, anergy may be the major mechanism for tolerance maintenance, as suggested in other models of tolerance (34).…”
Section: Discussionmentioning
confidence: 99%
“…5C). Therefore, anergy may be the major mechanism for tolerance maintenance, as suggested in other models of tolerance (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several types of regDCs, with similar functions but different phenotypes (13)(14)(15)(16)(17)(18), can be induced by a cytokine mixture that includes GM-CSF, IL-10, and TGF-b in vitro; however, these induction conditions do not accurately mimic the microenvironment in vivo, which involves a complex orchestration and regulation of cytokine production and cell-cell interaction. Previous reports showed that BM-MSCs could influence DC differentiation (8,9), and Cao's group (19) showed that endothelial splenic stroma could induce the differentiation of CD11b high Ia low regDCs from bone marrow hematopoietic stem/progenitor cells (BM-HPCs), but the induction of regDCs in vivo remains controversial.…”
mentioning
confidence: 99%
“…In animal models, the administration of 1-methyl-tryptophan, a small-molecule IDO inhibitor, into pregnant mice resulted in immediate rejection of an allogeneic fetus, confirming its role in maternal immune tolerance towards paternal alloantigens (Munn, Zhou et al 1998;Mellor and Munn 2004). In this manner, it has been shown that IDO not only contributes to maternal tolerance but can control allograft rejection (Grohmann, Orabona et al 2002;Cook, Bickerstaff et al 2008) and ameliorate autoimmune diseases as well Platten, Ho et al 2005). In addition, IDOmediated immunosuppression has been demonstrated to play a role in decreased immunosurveillance of tumor tissues and its inhibition by pharmacological agents such as 1-L-methyl-tryptophan (1-MT) results in improved anti-tumor responses (Hou, Muller et al 2007).…”
Section: Ido Competencementioning
confidence: 87%
“…Attempts have been made also to apply DCs transduced with constructs for both IL-10 and TGF-, which led to increased graft survival compared to single cytokine-expressing DCs (Gorczynski, Bransom et al 2000). Several experimental data confirmed an essential role of IDO and DCs in immunoregulation of allo-responses (Hainz, Jurgens et al 2007;Cook, Bickerstaff et al 2008). In a rat kidney transplantation model, allograft tolerance was induced by administration of an anti-CD28 Ab (Haspot, Seveno et al 2005).…”
Section: Tdcs In Transplantationmentioning
confidence: 95%